Indisciplina e sua relação com motivos, interesses e sentidos vinculados à atividade dos alunos: um estudo com uma classe de ensino médio da cidade de Medianeira-PR - Juliano, Joice Maria Maltauro [UNESP] (2015)
This dissertation reports the research which had as a general goal to evidence the relation between the conduct considered undisciplined by the school and the interests and reasons which guide the activity as well as the sense assigned to it by the student, using as reference the conducts considered disciplined. And, as specific goals, explain the dynamics of the learning activity done in class, identify the students' interests and reasons and the sense attributed by them to the activity which is developed in the classroom and verify what reasons, interests and sense are linked to conducts considered undisciplined and, in contrast, which are related to conducts considered disciplined.The research is based on the assumptions of cultural-historical theory and the theory of activity. The research is characterized as qualitative research conducted at Colégio Estadual João Manoel Mondrone, Medianeira - PR. The subjects of the research are six high school students of a 2nd grade class.The instruments used for data generation are the interview (with students), observationas support for the interpretation of the analyzed phenomenon, the questionnaire (for students) to compose the profile of the research subjects, and the collection of materials used by teachers to the development of classes, besides the literature search that provides the basic theoretical foundation for data interpretation.The analysis is carried out considering the following points: reason, interest and sense found by students whether doing or not the activities proposed by teachers in classes.The analysis of the gotten results allow us the following conclusions: (1) the interests of the group considered unruly students do not coincide with the purpose given to classes which intends to prepare students for going to the University: they are interested in finishing high school and keep on the profession they have already been working, unlike the students considered...